Twisted games - Huang, Ana (Huang, Ana. Twisted series, 2022)
Stoic, broody, and arrogant, elite bodyguard Rhys Larsen has two rules: 1) Protect his clients at all costs 2) Do not become emotionally involved. Ever. He has never once been tempted to break those rules ... until her. Bridget von Ascheberg. A princess with a stubborn streak and a hidden fire that reduces his rules to ash. She's nothing he expected and everything he never knew he needed. Day by day, inch by inch, she breaks down his defenses until he's faced with a truth he can no longer deny: he swore an oath to protect her, but all he wants is to ruin her. Because she's his. His princess. His forbidden fruit. His every depraved fantasy. Regal, strong-willed, and bound by the chains of duty, Princess Bridget dreams of the freedom to live and love as she chooses. But when her brother abdicates, she's suddenly faced with the prospect of a loveless, politically expedient marriage and a throne she never wanted. And as she navigates the intricacies-and treacheries-of her new role, she must also hide her desire for a man she can't have. Her bodyguard. Her protector. Her ultimate ruin. Theirs is a love that could destroy a kingdom ... and doom them both. Contains mature themes.